THE Student Perception of Assessment in the Teaching and Learning Process of Art Education - Tomsic Amon, Bea (Revija za elementarno izobraževanje, 2024)
This paper discusses the importance of the learning and teaching process in art education in light of the accepted methods for establishing criteria for evaluating student achievement. The complex experience of art education is difficult to measure based on scales that use ambiguous verbal categories and standardize the image of the student in an activity intended for the opposite: to express what is unique to each individual in an artistic way. Some assessment strategies are presented, as well as a questionnaire with various student opinions about assessment, alongside the factors that influence these opinions.
Keywords: art education, assessment, evaluation, learning styles, grades.